Hubungan Kekuatan Otot Lengan dan Fleksibilitas Bahu Terhadap Ketepatan Smash Ekstrakurikuler Bulutangkis - Rikki Ricardi; Titis Nurina; Firman Maulana (Indonesia Sport Journal, 2019)
The aim of this research is to prove the relationship between arm muscle strength and shoulder flexibility and smash accuracy in extracurricular SMPN 2 Cicurug. This study uses a survey method with test and measurement techniques. The population of this research is 16 badminton extracurricular members of SMPN 2 Cicurug. The research sample was all 16 badminton extracurricular members of SMPN 2 Cicurug. The sampling technique uses total sampling. Instruments used include: (1) Arm muscle strength test (2) Shoulder flexibility test (3) Smash accuracy test. Data analysis techniques used multiple correlation statistical data collection techniques. The results of the study, with calculations using the multiple correlation technique obtained Fcount (18.97)> Ftable (3.03) with a significance level of 0.05 then H0 is rejected, meaning that there is a relationship between arm muscle strength and shoulder flexibility to the accuracy of smashes in badminton at SMPN 2 Cicurug. Conclusions: (1) There is a significant relationship between arm muscle strength and smash accuracy at SMPN 2 Cicurug, (2) There is a significant relationship between shoulder flexibility and smash accuracy at SMPN 2 Cicurug, (3) There is a significant relationship between arm muscle strength and shoulder flexibility to the accuracy of the smash at SMPN 2 Cicurug.